PAC1 Deficiency Protects Obese Male Mice From Immobilization-Induced Muscle Atrophy by Suppressing FoxO–Atrogene Axis - Li, Qifang; Ishii, Kiyo-aki; Kamoshita, Kyoko; Takahashi, Kenta; Abuduwaili, Halimulati; Takayama, Hiroaki; Galicia-Medina, Cynthia M; Tanida, Ryota; Ko Oo, Hein; Gafiyatullina, Guzel; Yao, Xingyu; Abuduyimiti, Tuerdiguli; et al. (Endocrinology (Philadelphia), 2023)
Abstract Muscle atrophy is the cause and consequence of obesity. Proteasome dysfunction mediates obesity-induced endoplasmic reticulum (ER) stress and insulin resistance in the liver and adipose tissues. However, obesity-associated regulation of proteasome function and its role in the skeletal muscles remains underinvestigated. Here, we established skeletal muscle-specific 20S proteasome assembly chaperone-1 (PAC1) knockout (mPAC1KO) mice. A high-fat diet (HFD) activated proteasome function by ∼8-fold in the skeletal muscles, which was reduced by 50% in mPAC1KO mice. mPAC1KO induced unfolded protein responses in the skeletal muscles, which were reduced by HFD. Although the skeletal muscle mass and functions were not different between the genotypes, genes involved in the ubiquitin proteasome complex, immune response, endoplasmic stress, and myogenesis were coordinately upregulated in the skeletal muscles of mPAC1KO mice. Therefore, we introduced an immobilization-induced muscle atrophy model in obesity by combining HFD and immobilization. mPAC1KO downregulated atrogin-1 and MuRF1, together with their upstream Foxo1 and Klf15, and protected against disused skeletal muscle mass reduction. In conclusion, obesity elevates proteasome functions in the skeletal muscles. PAC1 deficiency protects mice from immobilization-induced muscle atrophy in obesity. These findings suggest obesity-induced proteasome activation as a possible therapeutic target for immobilization-induced muscle atrophy.